Ghana : Seventh and Eighth Reviews Under the Extended Credit Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Ghana's Seventh and Eighth Reviews Under the Extended Credit Facility Arrangement and Request for a Waiver of Nonobservance of Performance Criterion (PC). Ghana's macroeconomic performance has significantly improved in the last two years under the ECF-supported program. The elevated debt burden and fiscal risks from the financial and energy sectors limit policy space. The large loss of foreign exchange reserves in 2018 is a pointed reminder of Ghana's exposure to shifting investors' sentiment and external shocks, amplified by the government's still elevated financing needs. Ghana's legacy of political budget cycles will test the authorities' commitment to macroeconomic discipline and reform in 2020-a challenge that the authorities intend to face head on. Corrective measures have been put in place to address the PCs missed at end-June (three) and end-December (two) and the continuous PC on credit to the government by the Bank of Ghana.